Synthesis of Iron-Modified Biochar Derived from Rice Straw and Its Application to Arsenic Removal - Thi Hanh Nguyen; Thi Huong Pham; Hong Tham Nguyen Thi; Thi Nham Nguyen; Minh-Viet Nguyen; Trinh Tran Dinh; Minh Phuong Nguyen; Trung Quang Do; Thao Phuong; Thu Trang Hoang; Thanh Tung Mai Hung; Viet Ha Tran Thi (Journal of Chemistry)
A novel iron-modified biochar (FMBC) derived from rice straw was synthesized using FeCl3 modification for efficient As(V) removal from aqueous solution. FTIR and SEM-EDX analyses were carried out to determine the mechanism involved in the removal process and also demonstrated that Fe had loaded successfully on the surface of modified biochar. The iron-modified biochar showed higher arsenic removal ability than the raw biochar. The iron-modified biochar showed a maximum adsorption with an initial solution pH of 5.0. Moreover, for the tested biochar, the As(V) removal kinetics data were well fitted by the pseudo-second-order model. Furthermore, the As(V) removal data upon being well fitted by the Langmuir model showed the maximal removal capacity of 28.49 mg/g. The simple preparation process and high adsorption performance suggest that the iron-modified biochar derived from rice straw could be served as an effective, inexpensive, and environmentally sustainable adsorbent to replace typical granular activated carbon (AC) for As(III) removal from aqueous solution.